PEMBELAJARAN OUTDOOR DALAM MEMANFAATKAN MEDIA PEMBELAJARAN GEOGRAFI BERBASIS ALAM DI PANTAI TOBOLOLO - Herniita Pasongli; Eva Marthinu; Ramdani Salam (JURNAL GEOGRAFI, 2021)
With the study of geosphere phenomena that occur in coastal areas, it is very sad if learning is only carried out in class without bringing students to see and experience natural and social events directly in the real world. The objectives of this study were 1) to determine students' cognitive learning outcomes after carrying out outdoor learning in the Tobolo Beach Tourism object area and 2) to determine students' perceptions of using Tobololo Beach tourism objects as learning media. This study uses a combination of mixed methods design research with quantitative research methods as the primary method. The research subject is the biogeophysical environment and students. The data collection techniques used are, Observation Sheets, Interviews, Tests, and Questionnaires. Data analysis is using descriptive percentage. The research results obtained are; learning outcomes before carrying out nature-based outdoor learning are 93% categorized as incomplete. After the implementation of outdoor learning in the coastal tourist area of ​​Tobololo, the learning outcomes have increased, namely 100% with the complete category. The perceptions conveyed by students are also different before and after outdoor learning. The results of the analysis obtained that students' perceptions were categorized as good 17% and very good 83%. This nature-based outdoor learning is an alternative that can be used by teachers in improving learning outcomes. The results of student perceptions obtained in outdoor learning provide students with a happy atmosphere, motivate students, relax as well as being able to do recreation.